ANALISIS MANAJEMEN SYARIAH DI FRONT OFFICE DEPARTMENT SOFYAN INN HOTEL RANGKAYO BASA PADANG - ,, Firman (RC-INSTITUT, 2019)
This research is motivated by the small number of hotels in Padang city that use sharia management principles. This study is a descriptive study with a qualitative data approach using the survey method. Data collection techniques are carried out using the method of observation, interviews, and documentation. In this study using Snow-Ball Sampling which involved informants, namely: Human Resources Department, Front Office Supervisor Department and Front Office Staff, Department of Hotel Rangkayo Basa. Data is analyzed in reduction, namely summarizing, selecting and focusing on important things, and analyzing data obtained on the problem under study. The results of this study indicate that: 1) Management in terms of planning aspects has been well structured. Because the management has regulations that are in accordance with the principles of sharia hotel management and makes it in the form of Standard Operating Procedures (SOPs) which are used as guidelines for employees in working to ensure the implementation of hotel services in accordance with sharia principles. 2) Organizing Organizing employees is good, but the number of staff who work in one day is very little, making the staff have to embrace the work to be a reservation at the same time the receptionist at one time working time. But so far there have been no obstacles that disturb employees while doing their jobs. 3) AffordableFrom the aspect of direction, direction is carried out by supervision who is responsible for Front Office staff in the form of job evaluation and if needed, management will participate in employee direction. 4) Monitoring From the aspect of supervision, the Hotel management always supervises the front office staff by means of direct management down the field in supervising the work of each front office staff so that if an error is made by staff or miss communication with guests, the management will immediately handle it.